Analisis Penerapan Akuntansi Keperilakuan dalam Pengukuran Kinerja Pegawai Bagian Keuangan di Koperasi Kredit Sangosay Cabang Maumere - Oktavia Ririanti Dadi; Konstantinus Pati Sanga; Pipiet Niken Aurelia (Universitas 45 Surabaya, 2024)
This research aims to determine the application of behavioral accounting in the Maumere branch of the Sangosay credit cooperative regarding 4 important things, namely attitudes, emotions, motivation and perception. To determine the impact of behavioral accounting on employee performance. This research uses a qualitative method with a case study approach. The data collection techniques used were observation, interviews and documentation. The data analysis technique used in this research is using an interactive analysis model. This interactive analysis begins with the stages of data reduction, data presentation, and conclusion/verification. The activities are carried out in an interactive form with the data collection process as a cyclical process. The results of the research show that the Maumere branch of the Sangosay credit cooperative has not fully implemented behavioral accounting with 4 important indicators, namely attitude, emotion, motivation and perception. The results of research on the impact of behavioral accounting highlight that employee absenteeism at the Sangosay credit cooperative is still very high, and indirectly slows down the savings and loan service process and affects team efficiency at the Maumere branch of the Sangosay credit cooperative.